Učinkovitost protimalarične kemoprofilakse - analiza obolevanja študentov medicine Sekcije za tropsko in potovalno medicino Medicinske fakultete v Ljubljani na humanitarnih odpravah v trope v letih 1990-2005 - Bokal, Urška (Zdravniški vestnik, 2007)
Background The aim of this study was to assess the incidence of malaria among the homogenous population of medical students and young doctors, specifically educated in tropical medicine, travelling to the third world countries for electives of two to four months' duration with professional and humanitarian purposes. We focused on the efficiency of currently widely reccomended antimalarial chemoprophylaxis, especially mefloquine. Methods The data were collected by a questionnaire, analysis of medical documentation and medical examinations of elective participants after their return. Malaria was diagnosed either microscopically or on basis of typical clinical features, followed by marked improvement after antimalarial therapy. Results From 106 expedition members that were adherent to regular exposure prophylactic measures as well as recommended chemoprophylaxis, 28 (26%) reported malaria. 23 (82%) among them visited Africa and 23 (82%) were taking mefloquine for chemoprophylaxis. None suffered from complicated form of disease. No statistically significant differences in malaria morbidity with reference to travel destination, gender or weather season were found. Conclusions High incidence of malaria in our population could be partially explained by a relatively long period of travel in malaria hyperendemic regions. We carefullyexamined thepossibility of erroneous diagnosis of malaria as well as probable increase in mefloquine resistance in hyperendemic rural regions of Africa. Absence of complicated malaria proves the benefits of complete adherence to antimalarial exposure and chemoprophylaxis.
Keywords: Adult; Antimalarials; Antimalariki; Chemoprevention; Diagnosis; efficiency; Kemoprevencija; Malaria; Malarija; Odrasli; Potovanje; Prevention And Control; profilaksa; student; Students, Medical; študenti; Študenti medicine; Travel; Tropical Climate; Tropska klima; tropska medicina; učinkovitost